Molecular heterogeneity and analysis of the long-term survival of patients with gastrointestinal stromal tumors - N. N. Mazurenko; V. V. Yugay; I. V. Tsyganova; M. P. Nikulin; P. P. Arkhiri; O. A. Anurova; N. A. Kozlov; I. S. Stilidi (Успехи молекулярной онкологии)
Introduction. Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract the character diagnostic feature of which is CD117 (KIT) expression. GISTs are clinically diverse and have different genetic alterations that may have predictive and prognostic significance.Aim – the study of clinical, morphological and genetic features of GISTs to assess the overall survival (OS) of patients with various profiles of genetic disorders for elucidation the factors contributing to prognosis.Materials and methods. A total 244 GIST patients who received combined treatment were enrolled in the study and their clinical characteristics and mutational status of KIT, PDGFRA, BRAF were analyzed. SDH-deficient GISTs were detected using IHC-analysis of SDHB expression.Results. Stromal tumors developed in stomach (50 %), small intestine (37.7 %), colon or rectum (8.6 %), esophagus (0.4 %) and extraorganically (EGIST, 5.7 %). Overall survival correlated with gastric site (p = 0.005), tumor size <10 cm (p = 0,0001) and mitotic count HPF< 10 / 50 (p = 0.007). KIT mutations were found in 168 (68.9 %) and PDGFRA – in 31 (12.1 %) of GISTs, 14 novel mutations were detected. Mutations in KIT exon 11 were found in 140 (57.4 %) tumors, 10-year OS, 51 %, median 124 months. Patients with deletions had lower OS than patients with substitutions or duplications in KIT exon 11 (p = 0,023). The lowest OS was in patients with primary mutations in KIT exons 13 or 17 (median 28 months) and duplications in KIT exon 9 (median 71 months). There was a low OS of young patients with homozygous KIT mutations, mutations that begin in intron and two simultaneous KIT mutations. GISTs with PDGFRA mutations were located in stomach and had no metastases, 10-year OS, 63 %, median 175 months. KIT / PDGFRA mutations were not observed in 45 (18.4 %) patients (wild-type GIST), 10-year OS, 59 %, median 250 months. Wild-type GISTs with BRAF, NF1 mutations and SDH deficiency were detected. The better OS was demonstrated by patients with BRAFV600E (10-year ОS, 84 %, median 97 months) and SDH deficiency (10-year and 15-year OS, 82 %).Conclusion. Genetic analysis is necessary to clarify GIST prognosis and predict the effectiveness of targeted therapy. The clinical, morphological and genetic diversity of GISTs was confirmed. Wild-type GISTs with BRAF mutations and SDHdeficiency were identified in the Russian population for the first time. The long-term 10- и 15-year OS of GIST patients were evaluated.